2011
DOI: 10.21608/jpp.2011.85595
|View full text |Cite
|
Sign up to set email alerts
|

AMELIORATIVE EFFECT OF STIGMASTEROL ON THE PRODUCTIVITY OF Vicia faba PLANTS GROWN UNDER SALT STRESS.

Abstract: The present investigation was carried out to study the effect of post-emergence soil treatment with different salinity levels (0.0, 100, 150 and 200 mM NaCl) on growth, endogenous phytohormones, yield components and some biochemical activities of the yielded seeds of Vicia faba plants. The results indicated that increasing of salinity up to 200 mM showed significant decreases in growth parameters at fruiting stage and yield components. On the other hand, the levels of IAA, GA3 decreased, while ABA level increa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 42 publications
1
6
0
Order By: Relevance
“…Moreover, HA and gamma radiation application on chilling-stressed coriander plant were shown to increase proline content. These results were similarly demonstrated on irradiated coriander [ 53 ], Pisum sativum L. [ 77 ], and wheat [ 14 ] plants.…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…Moreover, HA and gamma radiation application on chilling-stressed coriander plant were shown to increase proline content. These results were similarly demonstrated on irradiated coriander [ 53 ], Pisum sativum L. [ 77 ], and wheat [ 14 ] plants.…”
Section: Discussionsupporting
confidence: 57%
“…Similar result concerning the effect of low dose of gamma radiation (20 Gy) on increasing the carbohydrate contents were reported on onion and potatoe [ 75 ] as well as Lupine [ 46 ]. HA was found to cause the accumulation of soluble sugars concomitantly with the increase in polysaccharides content and total carbohydrates in wheat plants grown in newly reclaimed soil [ 14 ]. Also, silicon has promoted photosynthetic pigments and hence total carbohydrates were increased.…”
Section: Discussionmentioning
confidence: 99%
“…Data presented in Table 2A and B, indicated that the increasing NaCl salinity concentration tended to decrease the inorganic mineral elements (K, S, P, Mg, Fe, Ca, Mn and Zn) contents and increased signicantly Na content compared with control plant. Also, Bassuony and al. (2008) found the content of K + ; Ca +2 and Mg +2 in Zea mays plant decreased significantly under salinity stress, compared with control.…”
Section: Mineralsmentioning
confidence: 86%
“…Similarly, the authors in [ 40 ] found that 150 or 200 ppm of stigmasterol resulted in the highest GA3 and IAA and the lowest ABA in both cultivars when compared to untreated plants. In addition, the authors in [ 41 , 42 ] stated that stigmasterol increases phytohormones, which can act as messengers and regulators of plant growth and development. The changes in the endogenous hormones were correlated with the changes in the activity of antioxidant enzymes, MDA, and proline, suggesting that the application of stigmasterol plays a central role in counteracting the injurious effects of gamma radiation.…”
Section: Discussionmentioning
confidence: 99%